The Use of Combining a Smartphone and a Digital Angle Ruler Technique to Assist Acetabular Cup Placement: A Clinical Study - Uthaicharatratsame, MD, Charoenwat; Pruetiworanan, MD, Suppawut; Suebpongsiri, MD, Pracha (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: To evaluate the percentage of acetabular cups that were correctly placed within the Lewinnek safe zone and the accuracy of the combined use of a smartphone and a digital angle ruler technique in assisting the placement of the acetabular cup by comparing the intraoperative values of acetabular cup inclination and anteversion to postoperative radiographic and CT scan measurements. Materials and Methods: This prospective observational study included 23 hips upon which were performed primary total hip arthroplasty through a lateral transgluteal approach in supine position. The combined use of a smartphone and a digital angle ruler technique was used for the reamers and cup positioning during acetabular reaming steps and final cup implantation. Postoperatively, a multislice CT scan was obtained at one month or later for cup anteversion measurement including a standard plain film of both hips in true anteroposterior position for cup inclination evaluation compared to the intraoperative values by using a paired t-test with a 0.05 level of significance. Results: The mean radiographic inclination (RI) angle from the digital angle ruler was 42.1º (SD 2.4). The mean RI angle from the postoperative radiographic measurement was 42.2º (SD 5.3). The mean paired difference was 0.39○ (SD 4.8), this difference was not significant (p = 0.97). The mean radiographic anteversion (RA) angle from the smartphone was 7.4º (SD 3.1).The mean RA from the postoperative CT scan was 11.9º (SD 5.9). The mean paired difference was 4.52○ (SD 4.3), this difference was significant (p< 0.05). The percentage of cup placements in the Lewinnek safe zone was 82.61%. Conclusion: The use of smartphone application combined with a digital angle ruler could provide an acceptable percentage of cup placements within the Lewennek safe zone and the inclination measurements were more accurate than the anteversion measurements.